Предмет: Алгебра,
автор: rrr323
Решите 2 уравнения 2(x-3)=-3(x+2)---------5x-(2x-9)=6+(x+3)
Ответы
Автор ответа:
0
5х-(2х-9)=6+(х+3)
5х-2х-9=6+х+3
5х-2х-х=6+3+9
2х=18
х=18:2
х=9
2(х-3)=-3(х+2)
2х-6=-3х+4
2х+3х=4+6
5х=10
х=10:5
х=2
5х-2х-9=6+х+3
5х-2х-х=6+3+9
2х=18
х=18:2
х=9
2(х-3)=-3(х+2)
2х-6=-3х+4
2х+3х=4+6
5х=10
х=10:5
х=2
Похожие вопросы
Предмет: Русский язык,
автор: bobkokanov
Предмет: Другие предметы,
автор: Аноним
Предмет: Другие предметы,
автор: dianazucenko
Предмет: Математика,
автор: dawa12315